Low signal intensities of MRI T1 mapping predict refractory diplopia in Graves' ophthalmopathy. (5th March 2020) - Matsuzawa, Kazuhiko; Izawa, Shoichiro; Kato, Ayumi; Fukaya, Kenji; Matsumoto, Kazuhisa; Okura, Tsuyoshi; Miyazaki, Dai; Kurosaki, Masamichi; Fujii, Shinya; Taniguchi, Shin‐ichi; Kato, Masahiko; Yamamoto, Kazuhiro
Abstract: Objective: In Graves' ophthalmopathy (GO), fibrosis in extraocular muscles (EOMs) may be related to intravenous glucocorticoid (ivGC)‐resistant diplopia. Signal intensity (SI) of magnetic resonance imaging (MRI) T1 mapping can quantify properties of EOM components, including fibrosis. We investigated EOM features of GO patients with diplopia using T1 mapping SI and the predictive value of T1 mapping SI in the response of diplopia to ivGCs. Design: We performed a cross‐sectional study that included 13 active GO patients, 34 inactive GO patients with history of diplopia, including 20 with a history of diplopia disappearance, 14 GO patients with refractory diplopia and 35 control subjects. In nine active GO patients, the relationship between T1 mapping SI at pretreatment and at diplopia outcome after ivGC treatment was prospectively investigated. Methods: T1 mapping SI of left and right inferior rectus and medial rectus muscles was measured in all participants. Results: T1 mapping SI in inactive GO patients with refractory diplopia was significantly lower than that of other groups in all evaluated EOMs. Diagnostic accuracy for refractory diplopia by T1 mapping SI in GO patients with a history of diplopia disappearance was excellent (AUC 0.89) compared with other assessments. Furthermore, among nine active GO patients, pretreatment T1 mapping SI in four patients with ivGC‐resistant diplopia tended to be low compared with the other five patients with improved diplopia. Conclusions: Low intensity T1 mapping in EOMs is likely to be associated with refractory diplopia and may be useful in predicting the response of diplopia to ivGCs.